Transparent conductive film

CN115769315BActive Publication Date: 2026-10-09TOYOBO CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202180044765.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-09-29
Filing Date
2021-08-05
Publication Date
2026-10-09
Estimated Expiration
2041-08-05

AI Technical Summary

Technical Problem

但是,以往的透明导电性薄膜若实施后述的笔重加压耐久性试验,则不充分

Benefits of technology

[0027] According to the present invention, a transparent conductive film can be provided that combines excellent pen sliding durability with excellent pen pressure durability, thereby providing high-resolution images. The resulting transparent conductive film is extremely useful for applications such as resistive touch panels.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115769315B_ABST
    Figure CN115769315B_ABST
Patent Text Reader

Abstract

The present application provides a transparent conductive film excellent in pen slide durability, pen heavy pressure durability, and high fineness when used in a touch panel. The transparent conductive film has a transparent conductive film of indium-tin composite oxide laminated on one face of a transparent plastic film substrate, the on-off resistance of the transparent conductive film of the transparent conductive film obtained by the following pen slide durability test is 10 kΩ or less, the increase rate of the surface resistance value of the transparent conductive film of the transparent conductive film obtained by further the following pen heavy pressure test is 1.5 or less, and the sum of the transmission image sharpness of the transparent conductive film under comb widths of 0.125 mm, 0.25 mm, 0.5 mm, 1.0 mm, and 2.0 mm is 250% or more and less than 500%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a transparent conductive film having a transparent conductive film of crystalline indium-tin composite oxide laminated on a transparent plastic film substrate, and particularly to a transparent conductive film with excellent pen sliding durability, pen pressure resistance, and high precision for use in resistive touch panels. Background Technology

[0002] Transparent conductive films, which are made by laminating transparent and low-resistance films onto a transparent plastic substrate, are widely used in the electrical / electronic fields as transparent electrodes for applications utilizing their conductivity, such as flat panel displays like liquid crystal displays and electroluminescent (EL) displays, and touch panels.

[0003] Resistive film touch panels are composed of fixed electrodes (with a transparent conductive film coated on a glass or plastic substrate) and movable electrodes (with a transparent conductive film coated on a plastic film), which are then superimposed on the top of a display. Pressing the film electrodes with a finger or stylus brings the transparent conductive films of the fixed and plastic electrodes into contact, providing input for position recognition of the touch panel. Compared to a finger, a stylus usually applies stronger force to the touch panel. If the stylus is used continuously for input, cracks, peeling, or abrasion may occur on the transparent conductive film on the film electrode side. Furthermore, if the touch panel is struck violently or very forcefully, applying the assumed strong force, cracks or peeling may occur on the transparent conductive film. To address these issues, a transparent conductive film with both excellent pen sliding durability and excellent pen pressure resistance is desired. Furthermore, high resolution is required for the image displayed on the touch panel.

[0004] As a means to improve pen sliding durability, there is a method to make the transparent conductive film on the thin-film electrode side crystalline (for example, see Patent Document 1). However, conventional transparent conductive films achieve excellent pen sliding durability by controlling the crystallinity of indium-tin composite oxides. However, conventional transparent conductive films are insufficient when subjected to the pen pressure durability test described later.

[0005] Prior art literature

[0006] Patent documents

[0007] Patent Document 1: Japanese Patent Application Publication No. 2004-071171 Summary of the Invention

[0008] -The problem the invention aims to solve-

[0009] The purpose of this invention is to provide a transparent conductive film that, in view of the aforementioned problems, exhibits excellent pen sliding durability and pen pressure resistance when used in touch panels, thereby providing high-resolution images.

[0010] -Methods for solving problems-

[0011] The present invention was made in view of the above-described situation, and the transparent conductive film of the present invention, which is able to solve the above-described problems, is composed of the following structure.

[0012] 1. A transparent conductive film comprising an indium-tin composite oxide transparent conductive film laminated on one side of a transparent plastic film substrate, wherein the on-resistance of the transparent conductive film obtained by the following pen sliding durability test is 10kΩ or less, and the increase rate of the surface resistance value of the transparent conductive film obtained by the following pen weight pressure test is 1.5 or less, and the sum of the transmitted image sharpness of the transparent conductive film at comb widths of 0.125mm, 0.25mm, 0.5mm, 1.0mm, and 2.0mm is 250% or more and less than 500%.

[0013] (Pen sliding durability test method)

[0014] The transparent conductive film was used as one panel. For the other panel, a transparent conductive film containing an indium-tin composite oxide film (tin oxide content: 10% by mass) with a thickness of 20 nm, formed on a glass substrate by sputtering, was used. The two panels were positioned with epoxy beads of 30 μm diameter facing each other, and the film-side panel and the glass-side panel were bonded together with double-sided tape of 170 μm thickness to create a touch panel. Next, a 2.5 N load was applied to a polyacetal pen (tip shape: 0.8 mmR), and a linear sliding test of 180,000 reciprocations was performed on the touch panel. In this test, the pen load was applied to the transparent conductive film surface.

[0015] The sliding distance at this point is 30 mm, and the sliding speed is 180 mm / s. After this sliding durability test, the conduction resistance (resistance value when the movable electrode (thin film electrode) is in contact with the fixed electrode) is measured when the sliding part is pressed with a pen load of 0.8 N.

[0016] (Pen weight pressure test method)

[0017] A transparent conductive film cut into 50mm × 50mm pieces was used as one panel. For the other panel, a transparent conductive film containing an indium-tin composite oxide film (tin oxide content: 10% by mass) formed on a glass substrate by sputtering with a thickness of 20nm was used. The two panels were arranged with epoxy beads of 30μm diameter facing each other, and the film-side panel was bonded to the glass-side panel using double-sided tape adjusted to a thickness of 120μm to create a touch panel. A 35N load was applied to a position 2.0mm from the end of the double-sided tape using a polyacetal pen (0.8mmR tip shape), and 10 linear slides (5 reciprocations) were performed parallel to the double-sided tape. In this test, the pen load was applied to the transparent conductive film surface. The sliding distance was 30mm, and the sliding speed was 20mm / s. Sliding was performed in a position without epoxy beads. After sliding, remove the transparent conductive film and measure the surface resistance at any five points on the sliding part (using the four-terminal method), then calculate the average value. When measuring the surface resistance, arrange the four terminals perpendicular to the sliding part, such that the sliding part appears between the second and third terminals. Divide the average surface resistance value of the sliding part by the surface resistance value of the non-sliding part (measured using the four-terminal method) and calculate the rate of increase in surface resistance.

[0018] 2. The transparent conductive film according to claim 1 above, wherein,

[0019] The transparent conductive film of indium-tin composite oxide has a crystal grain size of 10–100 nm, a crystallinity of 20–80%, contains 0.5–10% by mass tin oxide, and a thickness of 10–30 nm. When the three-dimensional surface roughness SRa of the transparent conductive film of indium-tin composite oxide is set as X, X is 1–100 nm. Furthermore, when the three-dimensional surface roughness SRa of the surface opposite to the transparent conductive film side on the transparent plastic film substrate is set as Y, (X... 3 +Y 3 ) 1 / 3 It is below 140nm.

[0020] 3. The transparent conductive film according to 1 or 2 above, wherein,

[0021] Even when an adhesion test is performed on the surface of the transparent conductive film (JIS K5600-5-6:1999), the transparent conductive film does not peel off. When a bending resistance test is performed on the transparent conductive film side of the indium-tin composite oxide transparent conductive film (JIS K5600-5-1:1999) and the bending part is observed with a 10x magnifying glass, the diameter of the mandrel that cracks or peels off is less than 20 mm.

[0022] 4. The transparent conductive film according to any one of claims 1 to 3 above, wherein,

[0023] The thickness of the transparent conductive film is 100–250 μm.

[0024] 5. The transparent conductive film according to any one of claims 1 to 4 above, wherein,

[0025] A curable resin layer is present between the transparent conductive film of indium-tin composite oxide and the transparent plastic film substrate.

[0026] -Invention Effects-

[0027] According to the present invention, a transparent conductive film can be provided that combines excellent pen sliding durability with excellent pen pressure durability, thereby providing high-resolution images. The resulting transparent conductive film is extremely useful for applications such as resistive touch panels. Attached Figure Description

[0028] Figure 1 This is a schematic diagram showing one example of the longest portion of a crystal grain in this invention.

[0029] Figure 2 This is a schematic diagram showing another example (the second one) of the longest portion of the crystal grain in this invention.

[0030] Figure 3 This is a schematic diagram showing another example (third example) of the longest portion of the crystal grain in this invention.

[0031] Figure 4 This is a schematic diagram showing another example (fourth) of the longest portion of the crystal grain in the present invention.

[0032] Figure 5 This is a schematic diagram illustrating the position of the center roller in an example of a sputtering apparatus preferably used in this invention. Detailed Implementation

[0033] The transparent conductive film of the present invention is a transparent conductive film in which an indium-tin composite oxide transparent conductive film is laminated on one side of a transparent plastic film substrate. The conductive film of the transparent conductive film obtained by the following pen sliding durability test has a conduction resistance of 10kΩ or less. Furthermore, the conductive film of the transparent conductive film obtained by the following pen weight pressure test has an increase rate of surface resistance of 1.5 or less. More preferably, the total transmittance image sharpness of the transparent conductive film with comb widths of 0.125mm, 0.25mm, 0.5mm, 1.0mm, and 2.0mm is 250% or more and less than 500%.

[0034] (Pen sliding durability test)

[0035] The transparent conductive film involved in this invention was used as one panel. For the other panel, a transparent conductive film containing an indium-tin composite oxide film (tin oxide content: 10% by mass) formed on a glass substrate by sputtering with a thickness of 20 nm was used. These two panels were arranged with epoxy beads of 30 μm diameter separating them, so that the transparent conductive films faced each other. The film-side panel and the glass-side panel were bonded together with double-sided tape of 170 μm thickness to create a touch panel. Next, a 2.5 N load was applied to a polyacetal pen (tip shape: 0.8 mmR), and a linear sliding test of 180,000 reciprocations was performed on the touch panel. In this test, the pen load was applied to the transparent conductive film surface involved in this invention. The sliding distance was 30 mm, and the sliding speed was 180 mm / s. After this sliding durability test, the conduction resistance (resistance value when the movable electrode (film electrode) contacts the fixed electrode) was measured when the sliding part was pressed with a pen load of 0.8 N.

[0036] (Pen weight pressure test)

[0037] As one panel, a transparent conductive film, cut into 50mm × 50mm pieces according to the present invention, was used. As another panel, a transparent conductive film comprising an indium-tin composite oxide film (tin oxide content: 10% by mass) formed on a glass substrate by sputtering with a thickness of 20nm was used. These two panels were arranged with epoxy beads of 30μm diameter between them, so that the transparent conductive films faced each other. The film-side panel was bonded to the glass-side panel using double-sided tape adjusted to a thickness of 120μm, thus creating a touch panel. A 35N load was applied to a position 2.0mm from the end of the double-sided tape using a polyacetal pen (0.8mmR at the tip), and 10 linear slides (5 reciprocations) were performed parallel to the double-sided tape. In this test, the pen load was applied to the transparent conductive film surface according to the present invention. The sliding distance was 30mm, and the sliding speed was 20mm / s. Sliding was performed in areas without epoxy beads. After sliding, remove the transparent conductive film and measure the surface resistance at any five points on the sliding part (using the four-terminal method), then calculate the average value. When measuring the surface resistance, arrange the four terminals perpendicular to the sliding part so that the sliding part appears between the second and third terminals. Divide the average surface resistance value of the sliding part by the surface resistance value of the non-sliding part (measured using the four-terminal method) and calculate the rate of increase in surface resistance.

[0038] The transparent conductive film of the present invention exhibits excellent pen sliding durability and pen pressure resistance. Pen sliding durability and pen pressure resistance are opposite properties. First, the pen sliding durability will be explained. The transparent conductive film of the indium-tin composite oxide with excellent pen sliding durability has high crystallinity and large crystal grain size. Crystallinity and crystal grain size will be explained. Regions with circular or polygonal shapes observed under a transmission electron microscope are defined as crystals (=grains) of the transparent conductive film, and other regions are defined as amorphous. High crystallinity indicates a high proportion of crystals. Large crystal grain size indicates a large circular or polygonal region observed under a transmission electron microscope. The transparent conductive film with high crystallinity has a high proportion of hard crystals, and the strain around the large crystal grains is large, thus the transparent conductive film is harder and exhibits excellent pen sliding durability. Next, the pen pressure resistance will be explained. Transparent conductive films of indium-tin composite oxides exhibiting excellent pen-weight pressure resistance require low crystallinity and small crystal grain size, resulting in low three-dimensional surface roughness. Regarding three-dimensional surface roughness, which will be explained later, transparent conductive films with low crystallinity have a high proportion of soft amorphous material, and the small crystal grain size results in less strain around the grains. Therefore, even when subjected to loads, cracks are less likely to form, leading to excellent pen-weight pressure resistance. As mentioned above, pen sliding durability and pen-weight pressure resistance are opposite properties. The research shows that by controlling the crystallinity and crystal grain size of the transparent conductive film, both pen sliding durability and pen-weight pressure resistance can be balanced. A transparent conductive film with a balance between pen sliding durability and pen-weight pressure resistance will be described.

[0039] In this invention, if the on-resistance of the transparent conductive film of the transparent conductive film, based on the pen sliding durability test, is 10kΩ or less, then even with continuous input to the touch panel using a pen, cracks, peeling, and wear on the transparent conductive film can be suppressed, which is therefore preferable. In one embodiment, the on-resistance can be 9.5kΩ or less, more preferably 5kΩ or less. For example, the on-resistance can be 3kΩ or less, 1.5kΩ or less, and preferably 1kΩ or less. If the on-resistance is 0kΩ, the pen sliding durability is excellent; in this invention, the on-resistance can also be 0kΩ. The on-resistance can, for example, be 3kΩ or more, or 5kΩ or more.

[0040] By keeping the on-resistance within such a range, even when continuously inputting onto the touch panel with a pen, cracks, peeling, and wear can be suppressed in the transparent conductive film.

[0041] In one approach, these upper and lower limits can also be combined appropriately.

[0042] In this invention, the increase rate of surface resistivity of the transparent conductive film based on the pen weight pressure test is preferably 1.5 or less. By possessing this characteristic, for example, even when a force stronger than that typically assumed is applied, cracking and peeling of the transparent conductive film can be suppressed. More preferably, the increase rate of surface resistivity is 1.2 or less, and particularly preferably 1.0 (no increase).

[0043] Here, the increase rate of the surface resistivity of the transparent conductive film involved in the present invention is preferably 1.0 or more.

[0044] In one embodiment, the on-resistance of the transparent conductive film in the transparent conductive film based on the pen sliding durability test is 0.05kΩ or more and 9.5kΩ or less, and the increase rate of the surface resistance value of the transparent conductive film in the transparent conductive film based on the pen pressure (durability) test is 1.0 or more and 1.5 or less.

[0045] As mentioned above, pen sliding durability and pen pressure durability are typically opposite properties. In this invention, both durability properties are balanced within a certain range. Furthermore, even with continuous input to the touch panel using a pen, cracking, peeling, and wear of the transparent conductive film are suppressed, and excellent durability is demonstrated under loads based on pen sliding and pen pressure. Additionally, the numerical ranges and values ​​described in this specification can be selected.

[0046] In this invention, if the sum of the transmitted image sharpness of the transparent conductive film with comb widths of 0.125 mm, 0.25 mm, 0.5 mm, 1.0 mm, and 2.0 mm is 250% or more and less than 500%, then a high-resolution image can be provided, which is therefore preferred. The greater the sum of the transmitted image sharpness, the higher the image sharpness, that is, the better the high resolution. More preferably, the sum of the transmitted image sharpness of the transparent conductive film is 300% or more. Even more preferably, the sum of the transmitted image sharpness of the transparent conductive film is 400% or more.

[0047] Additionally, in this manual, "comb width" refers to the width of the comb according to JIS-K7105.

[0048] In this invention, the transparent conductive film preferably has a crystal grain size of 10–100 nm and a crystallinity of 20–80% for an indium-tin composite oxide transparent conductive film. When the crystal grain size of the indium-tin composite oxide transparent conductive film is 10 nm or more, the transparent conductive film moderately hardens due to the strain around the grains, thus exhibiting excellent pen sliding durability, and is therefore preferred. More preferably, the crystal grain size of the indium-tin composite oxide transparent conductive film is 30 nm or more.

[0049] On the other hand, if the crystal grain size of the transparent conductive film of the indium-tin composite oxide is 100 nm or less, the transparent conductive film will not be too rigid due to the strain around the crystal grains. Therefore, it is preferred because of its excellent durability under heavy pressure. More preferably, the crystal grain size of the transparent conductive film of the indium-tin composite oxide is 90 nm or less.

[0050] In one embodiment, the crystal grain size of the transparent conductive film of the indium-tin composite oxide is greater than 30 nm and less than 95 nm, for example, greater than 40 nm and less than 90 nm.

[0051] When the crystallinity of the transparent conductive film of indium-tin composite oxide is 20% or more, it becomes moderately hardened due to the presence of hard crystals within the transparent conductive film, resulting in excellent pen sliding durability, and is therefore preferred. More preferably, the crystallinity of the transparent conductive film of indium-tin composite oxide is 25% or more. On the other hand, if the crystallinity of the transparent conductive film of indium-tin composite oxide is 80% or less, it contains a large amount of hard crystals, but since the transparent conductive film is not excessively hard, it exhibits excellent durability under pressure, and is therefore preferred.

[0052] In one embodiment, the crystallinity of the transparent conductive film of the indium-tin composite oxide is above 25% and below 78%, for example, above 25% and below 76%.

[0053] In this invention, when the three-dimensional surface roughness SRa of the transparent conductive film is set as X, X is preferably 1–100 nm. If X is 1–100 nm, the surface protrusions of the transparent conductive film are small, thus reducing the deformation of the surface protrusions during the pen weight pressure test, suppressing the formation of cracks in the transparent conductive film. Consequently, the presence of a few surface protrusions on the transparent conductive film also maintains the film's rollability, which is preferred. More preferably, X is 1–80 nm. Even more preferably, X is 1–65 nm.

[0054] The transparent conductive film of the present invention comprises an indium-tin composite oxide, preferably containing 0.5% by mass or more and 10% by mass of tin oxide. Tin oxide in the indium-tin composite oxide is equivalent to an impurity relative to indium oxide. The presence of tin oxide as an impurity increases the melting point of the indium-tin composite oxide. That is, since the presence of tin oxide as an impurity acts in the direction that hinders crystallization, it is an important factor that is strongly correlated with crystallinity such as crystal size and degree of crystallinity. If the content of tin oxide is 0.5% by mass or more, the surface resistance of the transparent conductive film becomes a practical level, which is preferred. More preferably, the content of tin oxide is 1% by mass or more, and particularly preferably 2% by mass or more. If the content of tin oxide is 10% by mass or less, crystallization is easily generated when adjusted to the semi-crystalline state described later, and the pen sliding durability becomes good, which is preferred. More preferably, the content of tin oxide is 8% by mass or less, further preferably 6% by mass or less, and particularly preferably 4% by mass or less. In addition, the surface resistance of the transparent conductive film of the present invention is preferably 50 to 900 Ω / □, more preferably 50 to 600 Ω / □.

[0055] In this invention, the thickness of the transparent conductive film is preferably 10 nm or more and 30 nm or less. The thickness of the transparent conductive film is an important factor that is strongly correlated with crystallinity, such as crystal grain size and degree of crystallinity. If the thickness of the transparent conductive film is 10 nm or more, the transparent conductive film will not have excessive amorphous properties, and it is easy to impart a suitable crystal grain size and degree of crystallinity to the semi-crystalline state described later, thus maintaining the pen's sliding durability, which is preferable. More preferably, the thickness of the transparent conductive film is 13 nm or more, and more preferably 16 nm or more. Furthermore, if the thickness of the transparent conductive film is 30 nm or less, the crystal grain size of the transparent conductive film will not be too large, and the degree of crystallinity will not be too high, making it easy to maintain the semi-crystalline state and maintaining the pen's durability under heavy pressure, which is preferable. More preferably, it is 28 nm or less, and even more preferably 25 nm or less.

[0056] In this invention, when the three-dimensional surface roughness SRa of the surface opposite to the transparent conductive film side on the transparent plastic film substrate is set to Y, if (X... 3 +Y 3 ) 1 / 3 For wavelengths below 140 nm, the total transmittance of transparent conductive films with comb widths of 0.125 mm, 0.25 mm, 0.5 mm, 1.0 mm, and 2.0 mm is greater than 250% and less than 500%, thus providing high-resolution images, and is therefore preferred. 3 +Y 3 ) 1 / 3 The smaller the value, the smaller the unevenness on both sides of the transparent conductive film. Therefore, it is confirmed and utilized that there is a tendency to increase the sharpness of the transmitted image to improve the straightness of the incident light on the transparent conductive film. More preferably (X 3 +Y3 ) 1 / 3 Below 120nm. Further preferred (X) 3 +Y 3 ) 1 / 3 Below 70nm. If (X) 3 +Y 3 ) 1 / 3 If the thickness is 1 nm or greater, there will be a few surface protrusions on the transparent conductive film, thus maintaining the film's rollability, which is preferred.

[0057] The transparent conductive film of this invention preferably does not peel off even when an adhesion test (JISK5600-5-6:1999) is performed on the surface of the transparent conductive film. A transparent conductive film that does not peel off in the adhesion test is preferred because the transparent conductive film and the layers in contact with it, such as the transparent plastic substrate and the curable resin layer, are in close contact. Therefore, even with continuous input to the touch panel using a pen, cracks, peeling, and abrasion of the transparent conductive film can be suppressed. Furthermore, even when a strong force, typically assumed to be greater than that used in normal applications, can suppress cracks and peeling of the transparent conductive film.

[0058] In this invention, the transparent conductive film preferably exhibits a bending resistance test (JIS K5600-5-1:1999) on its transparent conductive film side, and the diameter of the mandrel that causes cracking or peeling during bending, observed with a 10x magnifying glass, is less than 20 mm. If the mandrel diameter is less than 20 mm, the layer in contact with the transparent conductive film will not crack during a pen weight pressure test, and no cracks will be generated in the transparent conductive film; therefore, this is preferred. More preferably, it is 18 mm or less.

[0059] In one embodiment, the bending resistance test value can be 1 mm or more, for example, 8 mm or more, or 10 mm or more. In another embodiment, the bending resistance test value can be 13 mm or more, or 15 mm or more.

[0060] It is preferred because within such a range, the layer in contact with the transparent conductive film does not break during the pen weight pressure test, and no cracks are generated in the transparent conductive film.

[0061] In addition, it can provide a transparent conductive film that has both excellent pen sliding durability and excellent pen pressure durability.

[0062] The thickness of the transparent plastic film substrate for the transparent conductive film in this invention is preferably in the range of 100 to 250 μm, more preferably 130 to 220 μm. If the thickness of the plastic film is 100 μm or more, mechanical strength is maintained, and in particular, deformation relative to pen input is small when used in a touch panel, resulting in excellent pen sliding durability and pen pressure resistance; therefore, this is preferred. On the other hand, when the thickness is 250 μm or less, it is not necessary to significantly increase the load used for positioning during pen input when used in a touch panel.

[0063] The transparent conductive film of the present invention preferably has a curable resin layer between the transparent conductive film and the plastic film substrate. The presence of the curable resin layer disperses the increased adhesion force of the transparent conductive film and the force applied to it, thus suppressing cracks, peeling, and wear compared to the transparent conductive film in the pen sliding test, and further suppressing cracks and peeling compared to the transparent conductive film in the pen pressure test, therefore it is preferred.

[0064] The transparent conductive film of this invention has a crystallinity that is neither too high nor too low (such crystallinity is referred to as semi-crystalline or semi-crystalline). It is very difficult to stabilize a transparent conductive film to a semi-crystalline state. This is because the semi-crystalline state is the state where the rapid phase transition from amorphous to crystalline stops midway. Therefore, it is sensitive to parameters related to crystallinity, namely the moisture content in the film-forming atmosphere, especially the hydrogen-containing gases. Even a slight reduction in the hydrogen-containing gases and moisture content in the film-forming atmosphere results in approximately complete crystallinity (high crystallinity); conversely, a slight increase in the hydrogen-containing gases and moisture content results in amorphous state (low crystallinity).

[0065] The manufacturing method for obtaining the transparent conductive film of the present invention is not particularly limited, but the following manufacturing method is preferably exemplified.

[0066] Sputtering is a preferred method for forming a transparent conductive film of indium-tin composite oxide with crystalline structure on at least one side of a transparent plastic film substrate. To manufacture the transparent conductive film with high productivity, a so-called roller sputtering apparatus, which supplies a film roller and winds it into the shape of a film roller after film formation, is preferred. A preferred method involves introducing a hydrogen-containing gas (any hydrogen-containing gas, such as hydrogen, ammonia, or a hydrogen + argon mixture, except water) into a mass flow controller at the amount described below, then setting the film temperature during sputtering to below 0°C, using a sintering target containing 0.5 to 10% by mass of indium-tin composite oxide, adjusting the thickness of the transparent conductive film of indium-tin composite oxide to 10 to 30 nm, and forming the transparent conductive film on a transparent plastic film with a three-dimensional surface roughness SRa of 1 to 100 nm. The film-forming atmosphere during sputtering has the effect of hydrogen-containing gas hindering the crystallization of the transparent conductive film. When hydrogen is flowing through a film-forming atmosphere, the preferred value (hydrogen flow rate) ÷ (inert gas flow rate + hydrogen flow rate) × 100 (sometimes only the hydrogen concentration is stated) is 0.01 to 3.00%. The hydrogen concentration is, for example, 0.01% or more and 2.00%, or it can be 0.01% or more and 1.00% or less.

[0067] Maintaining the hydrogen concentration within such a range, for example, in either the on-resistance value of a pen sliding durability test or the pen pressure durability test, can help yield good results.

[0068] In addition, helium, argon, krypton, and xenon are examples of inert gases. When using a hydrogen-containing gas other than hydrogen, the amount of hydrogen atoms contained in the hydrogen-containing gas can be converted into the amount of hydrogen (= hydrogen molecules) for calculation. When the hydrogen-containing gas is precisely flowed in the film-forming atmosphere by a mass flow controller, by configuring the gas outlet so that the hydrogen-containing gas can be blown uniformly in a direction perpendicular to the length direction of the film roller, it is difficult to obtain a transparent conductive film with a mixture of highly crystalline and less crystalline parts. It is easy to obtain a uniform semi-crystalline transparent conductive film, thus it is possible to obtain a transparent conductive film with both excellent pen sliding durability and pen pressure durability. It is known that if there is more water in the film-forming atmosphere, the crystallinity of the transparent conductive film decreases. Therefore, the water content in the film-forming atmosphere is also an important factor. When using a hydrogen-containing gas, the midpoint value (the midpoint between the maximum and minimum value) of the ratio of water pressure in the film-forming atmosphere to the inert gas during sputtering is controlled to 1.0 × 10⁻⁶. -4 ~2.0×10 -3Furthermore, regarding the ratio of water pressure to inert gas in the film-forming atmosphere during sputtering, if the difference between the maximum and minimum values ​​from the start to the end of film formation is 1.0 × 10⁻⁶... -3 To maintain the uniformity of crystallinity of the transparent conductive film throughout its entire length, besides rotary pumps, turbomolecular pumps, and cryogenic pumps commonly used as exhaust devices for sputtering machines, if the following bombardment process and the limitation of the unevenness of the film roller end face are performed—that is, to reduce the amount of water released from the film during the formation of the transparent conductive film and to release water uniformly throughout the entire length of the film—precise control of the amount of water is not required, and this is therefore preferred. The central value of the water pressure to inert gas ratio depends somewhat on the tin oxide content in the indium-tin composite oxide transparent conductive film and the thickness of the transparent conductive film. When the amount of tin oxide added to the indium-tin composite oxide transparent conductive film is high and the transparent conductive film is thin, it is preferable to set the central value of the water pressure to inert gas ratio within the stated range to be low. Conversely, when the tin oxide content in the indium-tin composite oxide transparent conductive film is low or the transparent conductive film is thick, it is preferable to set the central value of the water pressure to inert gas ratio within the stated range to be high. Preferably, the film temperature during sputtering is below 0°C to form a transparent conductive film on a transparent plastic film. The film temperature during film formation is replaced by the set temperature of a temperature controller that adjusts the temperature of the central roller in contact with the traveling film. Here, Figure 5 This schematic diagram illustrates an example of a sputtering apparatus preferred for use in this invention, in which a traveling thin film 1 travels in partial contact with the surface of a central roller 2. An indium-tin sputtering target 4 is positioned via a chimney 3, and a thin film of indium-tin composite oxide is deposited and laminated on the surface of the thin film 1 traveling on the central roller 2. The central roller 2 is temperature-controlled by a temperature controller (not shown). If the film temperature is below 0°C, the release of impurity gases such as water and organic gases from the film that disperses the crystallinity of the transparent conductive film can be suppressed, thus facilitating the homogenization of the crystallinity of the transparent conductive film from the start to the end of film formation, which is preferable. When using a hydrogen-containing gas, the midpoint (the midpoint between the maximum and minimum values) of the ratio of the water pressure of the film-forming atmosphere to the inert gas during sputtering is preferably 1.0 × 10⁻⁶. -4 ~2.0×10 -3 If the ratio of water pressure to inert gas in the film-forming atmosphere during sputtering is within the specified range, the inhibition of crystallinity of the transparent conductive film by the hydrogen-containing gas will effectively function, which is therefore preferable. Furthermore, to achieve practical levels of surface resistance and total light transmittance of the transparent conductive film, it is preferable to add oxygen during sputtering. This manufacturing method primarily aims to eliminate the influence of water, a significant factor that disrupts the crystallinity of the transparent conductive film, on crystallinity by utilizing hydrogen-containing gas.

[0069] In controlling the moisture content during the formation of indium-tin composite oxides on plastic films, it is preferable to observe the actual moisture content during film formation rather than observing the vacuum level reached, for the following two reasons.

[0070] The first reason is that when film is formed by sputtering onto a plastic film, the film is heated and moisture is released from the film. As a result, the moisture content in the film-forming atmosphere increases, which is higher than the moisture content when the vacuum degree is reached. Therefore, the moisture content at the time of film formation is more accurate than the performance based on the vacuum degree.

[0071] The second reason concerns the application of apparatuses that feed large quantities of transparent plastic film. In such apparatuses, the film is fed using a film roller. If the film is fed into a vacuum chamber as a roller, water on the outer layer of the roller easily detaches, but water on the inner layer is difficult to detach. This is because the film roller stops when the vacuum level is reached, but moves during film formation, causing the inner layer of the roller, which contains a large amount of water, to be rolled out. Consequently, the moisture content in the film-forming atmosphere increases compared to the moisture content when the vacuum level is reached. In this invention, the moisture content in the film-forming atmosphere can be preferably controlled by observing the ratio of the water pressure of the film-forming atmosphere to the inert gas during sputtering.

[0072] Preferably, the thin film is subjected to a bombardment process before the formation of the transparent conductive film. The bombardment process refers to generating plasma by applying a voltage and discharging under a gas atmosphere where only an inert gas such as argon or a mixture of a reactive gas and an inert gas such as oxygen is introduced. Specifically, it is preferable to bombard the thin film using RF sputtering with a SUS target or the like. Since the thin film is exposed to plasma through the bombardment process, water and organic components are released from the film. This reduces the amount of water and organic components released during the formation of the transparent conductive film, thus facilitating the homogenization of the crystallinity of the transparent conductive film from the start to the end of film formation, which is preferable. Furthermore, since the bombardment process activates the layers at the junctions of the transparent conductive films, the adhesion of the transparent conductive film is improved, thereby enhancing pen sliding durability and pen pressure resistance.

[0073] In the film roller used for forming transparent conductive films, the height difference between the most convex and the most concave parts on the roller end face is preferably 10 mm or less. If it is 10 mm or less, the unevenness of the release method of water and organic components from the film end face is reduced when the film roller is put into the sputtering device. Therefore, the crystallinity of the transparent conductive film is easily homogenized from the beginning to the end of film formation, which is preferred.

[0074] In a method for forming a transparent conductive film of crystalline indium-tin composite oxide on at least one side of a transparent plastic film substrate, it is preferable to introduce oxygen during sputtering. Introducing oxygen during sputtering prevents adverse effects due to oxygen deficiency in the transparent conductive film of the indium-tin composite oxide, resulting in a lower surface resistance and higher overall light transmittance of the transparent conductive film. Therefore, to achieve practically usable surface resistance and overall light transmittance of the transparent conductive film, it is preferable to introduce oxygen during sputtering. Furthermore, the overall light transmittance of the transparent conductive film of the present invention is preferably 70-95%.

[0075] The transparent conductive film of the present invention is preferably formed by laminating an indium-tin composite oxide transparent conductive film on a transparent plastic film substrate, and then subjecting it to a heat treatment at 80–200°C for 0.1–12 hours in an oxygen-containing atmosphere. If the temperature is above 80°C, it is easier to slightly increase the crystallinity to form a semi-crystalline state, thus improving pen sliding durability, and is therefore preferred. If the temperature is below 200°C, it is preferred to ensure the planarity of the transparent plastic film.

[0076] <Transparent Plastic Film Substrate>

[0077] The transparent plastic film substrate used in this invention refers to a film obtained by melt extrusion or solution extrusion of organic polymers in a film-like form, followed by stretching, cooling, and thermal fixation in the length and / or width directions as needed. Examples of organic polymers include polyethylene, polypropylene, polyethylene terephthalate, polyethylene 2,6-naphthalenedicarboxylate, polyethylene terephthalate, polyethylene terephthalate, polybutylene terephthalate, nylon 6, nylon 4, nylon 66, nylon 12, polyimide, polyamide-imide, polyethersulfone, polyetheretherketone, polycarbonate, polyarylate, cellulose propionate, polyvinyl chloride, polyvinylidene chloride, polyvinyl alcohol, polyetherimide, polyphenylene sulfide, polyphenylene ether, polystyrene, syndiotactic polystyrene, norbornene polymers, etc.

[0078] Among these organic polymers, polyethylene terephthalate, polyethylene terephthalate, polybutylene terephthalate, polyethylene 2,6-naphthalenedicarboxylate, syndiotactic polystyrene, norbornene polymers, polycarbonate, and polyarylates are preferred. Furthermore, these organic polymers can be copolymerized in small amounts with monomers of other organic polymers, or blended with other organic polymers.

[0079] Without prejudice to the purpose of the present invention, the transparent plastic film substrate used in the present invention may be subjected to surface activation treatments such as corona discharge treatment, glow discharge treatment, flame treatment, ultraviolet irradiation treatment, electron beam irradiation treatment, and ozone treatment.

[0080] If a curable resin layer is coated onto a transparent plastic film substrate, the transparent conductive film and the curable resin layer are firmly bonded together, or the force applied to the transparent conductive film is dispersed. Therefore, cracks, peeling, and wear of the transparent conductive film can be suppressed during pen sliding tests, and further, cracks and peeling of the transparent conductive film can be suppressed during pen pressure tests, which is therefore preferred. Furthermore, if the transparent conductive film is formed on the surface of the curable resin layer to create an uneven surface, the actual contact area between the transparent conductive film and the glass is reduced during pen sliding tests. This improves the sliding properties between the glass surface and the transparent conductive film, increases pen sliding durability, and can be expected to improve the roll-up properties of the film roller and prevent Newton's rings. However, if the unevenness is too large, the deformation of the surface protrusions during pen pressure tests will increase, causing cracks in the transparent conductive film, which is not preferred. Therefore, when the three-dimensional surface roughness SRa of the transparent conductive film is set to X, X is preferably 1 to 100 nm as the surface unevenness. In addition, the curable resin layer can also be coated on both sides of the transparent plastic film substrate. When the three-dimensional surface roughness SRa of the cured resin layer on the side opposite to the surface where the transparent conductive film is formed is set to Y, Y is preferably set to 1 to 139 nm. Hereinafter, details of the cured resin layer will be described.

[0081] Furthermore, as a preferred curable resin layer used in this invention, there are no particular limitations on any resin that is cured by applying energy such as heating, ultraviolet irradiation, or electron beam irradiation; examples include silicone resin, acrylic resin, methacrylic resin, epoxy resin, melamine resin, polyester resin, and polyurethane resin. From a productivity point of view, an ultraviolet-curable resin as the main component is preferred.

[0082] Examples of such UV-curable resins include multifunctional acrylate resins such as acrylic or methacrylate polyols, diisocyanates, and multifunctional polyurethane acrylate resins synthesized from polyols and hydroxyalkyl esters of acrylic or methacrylate. Depending on the requirements, monofunctional monomers, such as vinylpyrrolidone, methyl methacrylate, and styrene, can be added to these multifunctional resins for copolymerization.

[0083] Furthermore, to improve the adhesion between the transparent conductive film and the curable resin layer, it is effective to treat the surface of the curable resin layer using the methods described below. Specific methods include: discharge treatment by glow discharge or corona discharge to increase carbonyl, carboxyl, and hydroxyl groups; and chemical treatment by acid or alkali to increase polar groups such as amino, hydroxyl, and carbonyl groups.

[0084] UV-curable resins are typically used with the addition of a photoinitiator. Known compounds that absorb ultraviolet light and generate free radicals can be used as photoinitiators without particular limitation; examples of such photoinitiators include various benzoin derivatives, benzophenone derivatives, and benzophenone derivatives. The amount of photoinitiator added is generally preferably 1 to 5 parts by weight per 100 parts by weight of the UV-curable resin.

[0085] Furthermore, in this invention, in addition to the curable resin as the main component, the curable resin layer and the functional layer preferably employ both inorganic and organic particles. By dispersing the inorganic and organic particles in the curable resin, unevenness can be formed on the surface of the curable resin layer and the functional layer, thereby improving the surface roughness over a wide area.

[0086] Examples of the inorganic particles mentioned above include silica. Examples of the organic particles mentioned above include polyester resin, polyolefin resin, polystyrene resin, and polyamide resin.

[0087] In addition to inorganic and organic particles, and besides the curable resin as a main component, it is preferable to also use a resin incompatible with the curable resin. By simultaneously using a small amount of incompatible resin in the curable resin matrix, phase separation can occur in the curable resin, dispersing the immiscible resin into particles. Through the dispersed particles of this immiscible resin, an uneven surface is formed on the surface of the curable resin layer, thereby improving the surface roughness over a wide area.

[0088] Examples of immiscible resins include polyester resins, polyolefin resins, polystyrene resins, and polyamide resins.

[0089] Here, as an example, the proportion of inorganic particles used in the curable resin layer directly beneath the transparent conductive film is shown. For every 100 parts by weight of the UV-curable resin, 0.1 to 20 parts by weight of inorganic particles is preferred, more preferably 0.1 to 15 parts by weight, and particularly preferably 0.1 to 12 parts by weight.

[0090] If the amount of inorganic particles mixed is 0.1 parts by mass or more and 30 parts by mass or less per 100 parts by mass of UV-curable resin, the protrusions formed on the surface of the cured resin layer will not be too small, the generation of cracks in the transparent conductive film will be suppressed, and high-resolution images can be provided. Furthermore, the presence of a few surface protrusions on the transparent conductive film also maintains the film's rollability, which is therefore preferred.

[0091] Here, as an example, the proportion of inorganic particles used in the curable resin layer on the side opposite to where the transparent conductive film is formed is shown. The inorganic particles are preferably 0.1 to 25 parts by mass, more preferably 0.1 to 15 parts by mass, and particularly preferably 0.1 to 12 parts by mass per 100 parts by mass of UV-curable resin. If the amount of inorganic particles is 0.1 to 25 parts by mass relative to 100 parts by mass of UV-curable resin, the protrusions formed on the surface of the curable resin layer are too small, effectively imparting a three-dimensional surface roughness, providing a high-resolution image, and thus having a small number of surface protrusions on the transparent conductive film, thereby maintaining the film's rollability, which is therefore preferable.

[0092] The UV-curable resin, photoinitiator, inorganic particles, organic particles, and resins immiscible with the UV-curable resin are dissolved in a common solvent to prepare the coating solution. There are no particular limitations on the solvents used; for example, alcohols such as ethanol and isopropanol, esters such as ethyl acetate and butyl acetate, ethers such as dibutyl ether and ethylene glycol monoethyl ether, ketones such as methyl isobutyl ketone and cyclohexanone, and aromatic hydrocarbons such as toluene, xylene, and naphtha can be used alone or in combination.

[0093] The concentration of the resin component in the coating solution can be appropriately selected considering factors such as viscosity appropriate for the coating method. For example, the combined amount of UV-curable resin, photoinitiator, and high molecular weight polyester resin in the coating solution is typically 20–80% by mass. Furthermore, other known additives, such as silicone-based leveling agents, can be added to the coating solution as needed.

[0094] In this invention, the prepared coating liquid is applied to a transparent plastic film substrate. The coating method is not particularly limited and can be any known method, such as rod coating, gravure coating, or reverse coating.

[0095] In the subsequent drying process, the solvent in the coating solution evaporates and is removed. During this process, the high molecular weight polyester resin, uniformly dissolved in the coating solution, becomes particles and precipitates into the UV-curable resin. After the coating is dried, the plastic film is irradiated with ultraviolet light, thereby causing the UV-curable resin to crosslink / cure and form a cured resin layer. In this curing process, the high molecular weight polyester resin particles are fixed in the hard coating layer, and protrusions are formed on the surface of the cured resin layer, increasing the surface roughness over a wide area.

[0096] Furthermore, the thickness of the cured resin layer is preferably in the range of 0.1 to 15 μm. More preferably, it is in the range of 0.5 to 10 μm, and particularly preferably, it is in the range of 1 to 8 μm. When the thickness of the cured resin layer is 0.1 μm or more, it is preferable to form sufficient protrusions. On the other hand, if it is 15 μm or less, the productivity is good, and therefore it is preferred.

[0097] Example

[0098] The present invention will now be described in more detail through examples, but the invention is not limited to these examples in any way. Furthermore, the various measurements and evaluations in the examples were performed using the methods described below.

[0099] (1) Total transmittance

[0100] The total transmittance was measured according to JIS-K7361-1:1997 using NDH-2000 manufactured by Nippon Denshoku Kogyo Co., Ltd.

[0101] (2) Surface resistivity

[0102] The determination was performed using a four-terminal method according to JIS-K7194:1994. The instrument used was a Lotesta AX MCP-T370 manufactured by Mitsubishi Chemical Analytech Co., Ltd.

[0103] (3) Average surface roughness SRa of the three-dimensional center plane

[0104] The three-dimensional center surface average surface roughness SRa is specified by ISO 25178 and is determined using a three-dimensional surface shape measuring device (Ryukyu Systems, R5500H-M100, measurement conditions: wave mode, measurement wavelength 560nm, objective lens 10x) via Burt scanning. Five measurements are taken, and their average value is calculated. The first decimal place in nm is rounded. Here, the three-dimensional surface roughness SRa of the transparent conductive film is designated as X, and the three-dimensional surface roughness SRa of the surface on the transparent plastic film substrate opposite to the transparent conductive film side is designated as Y.

[0105] (4) Crystal grain size

[0106] A thin film sample with a layer of transparent conductive film is cut into 1mm × 10mm pieces and adhered to the upper surface of a suitable resin block with the conductive film side facing out. After trimming, ultrathin sections are prepared approximately parallel to the film surface using a standard ultramicrotome technique.

[0107] The conductive film surface portion of the section without significant damage was observed using a transmission electron microscope (JEOL, JEM-2010) and photographed at an accelerating voltage of 200 kV and a direct magnification of 40,000x.

[0108] In the grains observed under a transmission electron microscope, the longest part of all grains was measured, and the average of these measurements was taken as the grain size. Here, in Figures 1-4 The diagram shows an example of a method for determining the longest part of a grain during measurement. Specifically, the longest part is determined based on the length of the straight line that maximizes the measurement of the grain size of each grain.

[0109] (5) Thickness of the transparent conductive film (film thickness)

[0110] A thin film sample with a stacked transparent conductive film layer was cut into 1mm × 10mm pieces and embedded in epoxy resin for electron microscopy. The sample was then fixed on the sample holder of an ultramicrotome, and a thin section parallel to the short side of the embedded sample was prepared. Next, at a non-damaged area of ​​the film on this section, a transmission electron microscope (JEOL, JEM-2010) was used to take photographs at an accelerating voltage of 200kV, in bright field, and at a magnification of 10,000x. The film thickness was determined from the obtained photographs.

[0111] (6) Pen sliding durability test

[0112] The transparent conductive film involved in this invention is used as one panel. For the other panel, a transparent conductive film comprising an indium-tin composite oxide film (tin oxide content: 10% by mass) formed on a glass substrate by sputtering with a thickness of 20 nm is used. These two panels are arranged with epoxy beads of 30 μm diameter between them, so that the transparent conductive films face each other, to create a touch panel. Next, a linear sliding test of 180,000 reciprocations is performed on the touch panel using a polyacetal pen (tip shape: 0.8 mmR) with a load of 5.0 N. In this test, the pen load is applied to the transparent conductive film surface involved in this invention. The sliding distance is 30 mm, and the sliding speed is 180 mm / s. After this sliding durability test, the on-resistance (resistance value when the movable electrode (film electrode) contacts the fixed electrode) when the sliding part is pressed with a pen load of 0.8 N is measured. The on-resistance is preferably 10 kΩ or less.

[0113] In addition, in the comparative examples, the thin films from each comparative example were used instead of the transparent conductive thin films involved in the present invention.

[0114] (7) Pen weight pressure test

[0115] One panel uses a transparent conductive film cut into 50mm × 50mm pieces, and the other panel uses a transparent conductive film comprising an indium-tin composite oxide film (tin oxide content: 10% by mass) formed on a glass substrate by sputtering, with a thickness of 20nm. These two panels are arranged with epoxy beads of 30μm diameter between them, so that the transparent conductive films face each other. A double-sided tape of 120μm thickness is used to bond the film-side panel to the glass-side panel, thus creating a touch panel. A 35N load is applied to a position 2.0mm from the end of the double-sided tape using a polyacetal pen (0.8mmR at the tip), and 10 linear slides (5 reciprocations) are performed parallel to the double-sided tape. In this test, the pen load is applied to the transparent conductive film surface of the present invention. The sliding distance is 30mm, and the sliding speed is 20mm / second. Sliding is performed in areas without epoxy beads. After sliding, remove the transparent conductive film and measure the surface resistance at any five points on the sliding part (using the four-terminal method), then calculate the average value. When measuring the surface resistance, arrange the four terminals perpendicular to the sliding part so that the sliding part appears between the second and third terminals. Divide the average surface resistance value of the sliding part by the surface resistance value of the non-sliding part (measured using the four-terminal method) and calculate the rate of increase in surface resistance.

[0116] In addition, in the comparative examples, the thin films from each comparative example were used instead of the transparent conductive thin films involved in the present invention.

[0117] (8) Determination of the tin oxide content in the transparent conductive film

[0118] Cut a sample (approximately 15cm) 2 Add 20 ml of 6 mol / L hydrochloric acid to a quartz Erlenmeyer flask and seal with a thin film to prevent acid evaporation. Let it stand at room temperature for 9 days while agitating occasionally to allow the transparent conductive film to dissolve. Remove the residual film, and use the hydrochloric acid containing the dissolved film as the assay solution. The In and Sn concentrations in the solution were determined using an ICP-C luminescence analyzer (manufacturer: Rigaku; device type: CIROS-120EOP) via calibration curve method. The wavelengths selected for each element were those with high sensitivity and no interference. Furthermore, commercially available In and Sn standard solutions were used.

[0119] (9) Adhesion test

[0120] Implemented in accordance with JIS K5600-5-6:1999.

[0121] (10) Bending resistance test

[0122] Implemented according to JIS K5600-5-1:1999. Where the mandrel diameter does not crack or peel up to 13 mm, the bending resistance test is not performed above that, and all are recorded as 13 mm.

[0123] (11) Transmitted image sharpness test

[0124] According to JIS-K7105, the transmitted image sharpness of transparent conductive films with comb widths of 0.125 mm, 0.25 mm, 0.5 mm, 1.0 mm, and 2.0 mm was measured, and the sum of the transmitted image sharpness for each comb width was calculated. The measuring instrument used was the Suga ICM-1T image sharpness measuring instrument.

[0125] The transparent plastic film substrate used in the examples and comparative examples was a biaxially oriented transparent PET film (manufactured by Toyobo Co., Ltd., A4380, thicknesses listed in Tables 1 and 2) with easily adhesive layers on both sides. As a curable resin layer, silica particles (manufactured by Nissan Chemical Co., Ltd., SNOWTEXZL) in amounts listed in Tables 1 and 2 were mixed into 100 parts by mass of an acrylic resin (manufactured by Daihiseki Chemical Co., Ltd., SEIKA Beam (registered trademark) EXF-01J) containing a photoinitiator. A toluene / MEK (8 / 2 by mass) mixed solvent was added to achieve the solids concentration values ​​listed in Tables 1 and 2. The mixture was stirred until homogeneous and dissolved, thus preparing a coating solution (hereinafter referred to as coating solution A). The prepared coating solution was applied using a Mayer rod to achieve a coating thickness of 5 μm. After drying at 80°C for 1 minute, the sample was irradiated with ultraviolet light (300 mJ / cm²) using an ultraviolet irradiation device (EYEGRAPHICS, UB042-5AM-W model). 2 This process allows the coating to cure. Furthermore, a curable resin layer is applied to both sides of the transparent plastic substrate.

[0126] (Examples 1-8)

[0127] Each embodiment was implemented under the conditions shown in Table 1, as follows.

[0128] A thin film was placed into the vacuum chamber, and the vacuum was evacuated to 1.5 × 10⁻⁶. -4 Pa. Next, after introducing oxygen, argon as an inert gas and hydrogen as a hydrogen-containing gas are introduced at the concentrations listed in Table 1 to make the total pressure 0.6 Pa.

[0129] With 3W / cm 2Power is applied to an indium-tin oxide composite sintering target or an indium oxide sintering target without tin oxide, and a transparent conductive film is formed by DC magnetron sputtering. The film thickness is controlled by varying the speed at which the film passes over the target. Furthermore, the ratio of moisture pressure to inert gas in the sputtering atmosphere is measured using a gas analyzer (Inficon, Transpector XPR3). At the level of each embodiment, to adjust the ratio of moisture pressure to inert gas in the sputtering atmosphere, the temperature of the heat carrier of the temperature controller, which controls the temperature of the film contacting the moving center roller, was adjusted according to the presence or absence of a bombardment process, the unevenness of the film roller end face, and the temperature of the film contacting the moving center roller, as shown in Table 1. The midpoint between the maximum and minimum temperatures from the start of film formation on the film roller to the end of film formation is recorded as the midpoint value in Table 1.

[0130] The films with the transparent conductive films deposited and laminated were subjected to the heat treatment described in Table 1, and then measurements were performed. The measurement results are shown in Table 1.

[0131] (Comparative Examples 1-9)

[0132] Under the conditions described in Table 1, transparent conductive films were prepared and evaluated in the same manner as in Example 1. In Comparative Example 7, no curable resin layer was provided. In Comparative Example 8, the thickness of the curable resin layer coating was adjusted to 20 μm. The results are shown in Table 2.

[0133] [Table 1A]

[0134]

[0135] [Table 1B]

[0136]

[0137] [Table 2A]

[0138]

[0139] [Table 2B]

[0140]

[0141] As described in Tables 1A and 1B, the transparent conductive films described in Examples 1 to 8 exhibit excellent pen sliding durability, pen pressure resistance, and high precision, possessing all these characteristics. However, as described in Table 2, Comparative Examples 1 to 9 do not fully meet the requirements for pen sliding durability, pen pressure resistance, and high precision.

[0142] -Industrial Availability-

[0143] As described above, according to the present invention, it is possible to produce a transparent conductive film with excellent pen sliding durability, pen pressure resistance, and high precision, which is extremely useful for applications such as resistive film touch panels.

[0144] -Explanation of Figure Markers-

[0145] 1. Film

[0146] 2. Center Roller

[0147] 3. Chimney

[0148] 4. Targets for indium-tin composite oxides.

Claims

1. A transparent conductive film comprising an indium-tin composite oxide transparent conductive film laminated on one side of a transparent plastic film substrate, wherein the conductive film has a conduction resistance of 10kΩ or less as obtained by a pen sliding durability test, and the surface resistance of the transparent conductive film has an increase rate of 1.5 or less as obtained by a pen pressure test, and the total transmittance image sharpness of the transparent conductive film at comb widths of 0.125mm, 0.25mm, 0.5mm, 1.0mm, and 2.0mm is 250% or more and less than 500%. In the pen sliding durability test method The transparent conductive film is used as one panel, and a transparent conductive film comprising an indium-tin composite oxide film is used as another panel. This indium-tin composite oxide film is formed on a glass substrate by sputtering and has a thickness of 20 nm, wherein the tin oxide content is 10% by mass. Two panels are arranged with epoxy beads of 30 μm diameter between them, so that the transparent conductive film is facing each other. The film-side panel and the glass-side panel are bonded together with double-sided tape of 170 μm thickness to create a touch panel. Next, a 2.5N load was applied to the polyacetal pen, and it underwent 180,000 reciprocating linear sliding tests on the touch panel. The shape of the pen's tip was 0.8mmR. In this experiment, a pen load was applied to the surface of the transparent conductive film, with a sliding distance of 30 mm and a sliding speed of 180 mm / s. After the pen's sliding durability test, the conduction resistance was measured when the sliding part was pressed with a pen load of 0.8 N. This conduction resistance is the resistance value when the movable electrode, which serves as a thin-film electrode, is in contact with the fixed electrode. In the pen weight pressure test method The transparent conductive film, cut into 50mm × 50mm pieces, is used as one panel. Another panel uses a transparent conductive film comprising an indium-tin composite oxide film, which is formed on a glass substrate by sputtering and has a thickness of 20nm, wherein the tin oxide content is 10% by mass. Two panels are arranged with epoxy beads of 30 μm diameter between them, so that the transparent conductive film is facing each other. The film-side panel is then bonded to the glass-side panel using double-sided tape adjusted to a thickness of 120 μm, thus creating a touch panel. A pen made of polyacetal was used to apply a 35N load to a position 2.0mm from the end of double-sided tape, and the pen was slid parallel to the tape 10 times (5 reciprocating strokes) in a straight line. The tip of the pen had a radius of 0.8mm. In this experiment, a pen load was applied to the surface of the transparent conductive film, with a sliding distance of 30 mm and a sliding speed of 20 mm / s. The film was slid along a section without epoxy beads. After sliding, the transparent conductive film was removed, and the surface resistance at any five points on the sliding section was measured using the four-terminal method. The average value was then calculated. When measuring surface resistivity, four terminals are arranged in a direction perpendicular to the sliding part, such that the sliding part appears between the second and third terminals. The rate of increase in surface resistance is calculated by dividing the average surface resistance value of the sliding part by the surface resistance value of the non-sliding part measured using the 4-terminal method. The transparent conductive film of indium-tin composite oxide has a crystal grain size of 10–100 nm, a crystallinity of 20–80%, contains 0.5–10% by mass tin oxide, and has a thickness of 10–30 nm. When the three-dimensional surface roughness SRa of the transparent conductive film of indium-tin composite oxide is set as X, where X is 1–100 nm, and the three-dimensional surface roughness SRa of the surface opposite to the transparent conductive film side on the transparent plastic film substrate is set as Y, (X) 3 +Y 3 ) 1 / 3 It is below 140nm.

2. The transparent conductive film according to claim 1, wherein, Even when an adhesion test (JIS K5600-5-6:1999) is performed on the surface of the transparent conductive film, the transparent conductive film does not peel off. When a bending resistance test (JIS K5600-5-1:1999) is performed on the transparent conductive film side of the indium-tin composite oxide transparent conductive film and the bending part is observed with a 10x magnifying glass, the diameter of the mandrel that cracks or peels off is less than 20 mm.

3. The transparent conductive film according to claim 1 or 2, wherein, The thickness of the transparent conductive film is 100–250 μm.

4. The transparent conductive film according to claim 1 or 2, wherein, A curable resin layer is present between the transparent conductive film of indium-tin composite oxide and the transparent plastic film substrate.

5. The transparent conductive film according to claim 3, wherein, A curable resin layer is present between the transparent conductive film of indium-tin composite oxide and the transparent plastic film substrate.

Citation Information

Patent Citations

  • Transparent conductive laminate for touch panel

    JP2004071171A

  • Transparent conductive film

    CN108292183A

  • Transparent electrically conductive film, transparent electrically conductive sheet and touch panel

    JP2002163933A